2011
DOI: 10.4103/0255-0857.76527
|View full text |Cite
|
Sign up to set email alerts
|

Sepsis due to linezolid resistant Staphylococcus cohnii and Staphylococcus kloosii: First reports of linezolid resistance in coagulase negative staphylococci from India

Abstract: Linezolid, a viable alternative to vancomycin against methicillin resistant staphylococcal isolates, has been in use for a decade around the globe. However, resistance against staphylococci remains extremely rare and unreported from most of the Asian countries. Herein, we report two cases of linezolid resistant, coagulase negative staphylococcal sepsis for the first time from India. The first case was an 18-year-old burn patient, who, after a major graft surgery, landed in sepsis, and linezolid resistant Staph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 30 publications
(23 citation statements)
references
References 12 publications
1
21
0
1
Order By: Relevance
“…[3] The first case linezolid-resistant staphylococci appeared within 1 year after linezolid was approved for use for treatment. [5] Here we report two linezolidresistant coagulase negative staphylococcal strains which were isolated in June 2010 at our hospital. [5] Here we report two linezolidresistant coagulase negative staphylococcal strains which were isolated in June 2010 at our hospital.…”
Section: Linezolid-resistantmentioning
confidence: 89%
“…[3] The first case linezolid-resistant staphylococci appeared within 1 year after linezolid was approved for use for treatment. [5] Here we report two linezolidresistant coagulase negative staphylococcal strains which were isolated in June 2010 at our hospital. [5] Here we report two linezolidresistant coagulase negative staphylococcal strains which were isolated in June 2010 at our hospital.…”
Section: Linezolid-resistantmentioning
confidence: 89%
“…(MRS) strains with intrinsic resistance to methicillin and all beta-lactam antibiotics are emerging pathogens in hospitalized diabetic patients. [27] Linezolid, a novel synthetic antibiotic, is considered one of the few effective ways to treat severe methicillin-resistant infections in critically ill patients. Recently, linezolid resistance is reported in our country which may be a consequence of prolonged and injudicious use of this drug[2728] and is an imperative threat to lose an effective and safe drug for treating MRS. HLAR in Enterococcus spp.…”
Section: Discussionmentioning
confidence: 99%
“…Although linezolid resistance in S. aureus is uncommon, emergence has been shown from some parts of the world [33]. From India, first case report of linezolid resistance was published in 2011 from Kashmir [34]. Present research has found 0.9% (3) VRSA in the MRSA, comparatively higher than that shown from north part of India [35].…”
Section: S Aureus Is a Leading Pathogen In Hospital Acquired Infectimentioning
confidence: 73%